THREE-DIMENSIONAL VISUALISATION OF THE GEOPHYSICAL INFORMATION FOR THE DECISION OF APPLIED PROBLEMS - Alexander Vasil'evich Shapovalov; Vitaly Alexandrovich Shapovalov (Наука. Инновации. Технологии, 2022)
In article the description of software of display of volume meteorological objects (clouds) on the three-dimensional electronic globe is resulted. The data of meteorological radars at display corresponds to real position of a radar station on a terrestrial surface, a substrate is the district map where remote supervision of overcast are carried out. The software of 3D visualisation of the radar-tracking meteorological information developed by authors allows to receive new representations about thundenstorm, their structure, interaction developing of convective cells.